Integration site-dependent HIV-1 promoter activity shapes host chromatin conformation - Collora, Jack A.; Ho, Ya-Chi (Genome Research, 2023)
HIV-1 integration introduces ectopic transcription factor binding sites into host chromatin. We postulate that the integrated provirus serves as an ectopic enhancer that recruits additional transcriptional factors to the integration locus, increases chromatin accessibility, changes 3D chromatin interactions, and enhances both retroviral and host gene expression. We used 4 well-characterized HIV-1-infected cell line clones having unique integration sites and low to high levels of HIV-1 expression. Using single-cell DOGMA-seq, which captured the heterogeneity of HIV-1 expression and host chromatin accessibility, we found that HIV-1 transcription correlated with HIV-1 accessibility and host chromatin accessibility. HIV-1 integration increased local host chromatin accessibility within ~5-30 kb distance. CRISPRa and CRISPRi-mediated HIV-1 promoter activation and inhibition confirmed integration site–dependent HIV-1-driven changes of host chromatin accessibility. HIV-1 did not drive chromatin confirmation changes at the genomic level (by Hi-C) or the enhancer connectome (by H3K27ac HiChIP). Using 4C-seq to interrogate HIV-1-chromatin interactions, we found that HIV-1 interacted with host chromatin ~100–300 kb from the integration site. By identifying chromatin regions having both increased transcription factor activity (by ATAC-seq) and HIV-1-chromtain interaction (by 4C-seq), we identified enrichment of ETS, RUNT, and ZNF-family transcription factor binding that may mediate HIV-1-host chromatin interactions. Our study found that HIV-1 promoter activity increased host chromatin accessibility, increased HIV-1-host chromatin interactions in an integration site–dependent manner, within the existing chromatin boundaries.
10.1101/gr.277698.123